High-Fructose Diet Increases Inflammatory Cytokines and Alters Gut Microbiota Composition in Rats - Yong Wang; Wentao Qi; Ge Song; Shaojie Pang; Zhenzhen Peng; Yong Li; Panli Wang (Mediators of Inflammation)
High-fructose diet induced changes in gut microbiota structure and function, which have been linked to inflammatory response. However, the effect of small or appropriate doses of fructose on gut microbiota and inflammatory cytokines is not fully understood. Hence, the abundance changes of gut microbiota in fructose-treated Sprague-Dawley rats were analyzed by 16S rRNA sequencing. The effects of fructose diet on metabolic disorders were evaluated by blood biochemical parameter test, histological analysis, short-chain fatty acid (SCFA) analysis, ELISA analysis, and Western blot. Rats were intragastrically administered with pure fructose at the dose of 0 (Con), 2.6 (Fru-L), 5.3 (Fru-M), and 10.5 g/kg/day (Fru-H) for 20 weeks. The results showed that there were 36.5% increase of uric acid level in the Fru-H group when compared with the Con group. The serum proinflammatory cytokines (IL-6, TNF-α, and MIP-2) were significantly increased (P<0.05), and the anti-inflammatory cytokine IL-10 was significantly decreased (P<0.05) with fructose treatment. A higher fructose intake induced lipid accumulation in the liver and inflammatory cell infiltration in the pancreas and colon and increased the abundances of Lachnospira, Parasutterella, Marvinbryantia, and Blantia in colonic contents. Fructose intake increased the expressions of lipid accumulation proteins including perilipin-1, ADRP, and Tip-47 in the colon. Moreover, the higher level intake of fructose impaired intestinal barrier function due to the decrease of the expression of tight junction proteins (ZO-1 and occludin). In summary, there were no negative effects on body weight, fasting blood glucose, gut microbiota, and SCFAs in colonic contents of rats when fructose intake is in small or appropriate doses. High intake of fructose can increase uric acid, proinflammatory cytokines, intestinal permeability, and lipid accumulation in the liver and induce inflammatory response in the pancreas and colon.